Laparoscopic urorectal fistula repair: value of the salvage prostatectomy and review of current approaches - Gözen, Ali Serdar; Rassweiler, Jens (Journal of endourology, 2012)
Background and Purpose: The surgical approach and repair for urorectal fistula (URF) is a challenging task. A variety of techniques have been described to treat URFs, and the laparoscopic approach has been approved as an efficient tool for even some complex fistulas. We aimed to report our laparoscopic experience for complex URF repair with special emphasis on salvage prostatectomy.Patients and Methods: The study included four men (59-75 years), with laparoscopic repair for complex URFs. URF developed after transurethral resection of the prostate in patients 2 and 3 and after radical prostatectomy in patient 4. Patient 1 had received combined radiotherapy and chemotherapy for the rectal carcinoma; a prostatic abscess developed that resulted at the end in URF. Laparoscopic salvage prostatectomy was performed for patients 1 and 2. A transvesical laparoscopic approach was performed for patient 3, and a transperitoneal transvesical technique was performed for patient 4. A tunica vaginalis flap was used for patient 1, and peritoneal interposition flaps were developed in patients 2 and 4 mL, and no patients needed intraoperative blood transfusion. Postoperative hospital stay was 12 to 34 days. The urethral catheter was removed on postoperative day 11 to 32, and cystography showed no leakage of contrast except in patient 1.Conclusions: Laparoscopic URF repair is safe and efficacious in experienced hands even in complex cases, and salvage laparoscopic prostatectomy seems like a valuable operative option. The technique requires advanced experience, however, particularly with pelvic surgery and intracorporeal suturing.